Cost-effectiveness analysis of Tumor Treating Fields treatment in Chinese patients with metastatic non-small cell lung cancer - Pei, Zhengda; Xiao, Ningping; Yang, Pei (Frontiers in Public Health, 2024)
Background: The LUNAR trial demonstrated the significant efficacy and safety of Tumor Treating Fields (TTFields) plus standard-of-care (SOC) (immune checkpoint inhibitor [ICI] and docetaxel [DTX]) for patients with previously treated metastatic non-small cell lung cancer (mNSCLC). However, it remains uncertain as to whether the high costs are justified by the corresponding survival benefits. Here, the cost-effectiveness of using TTFields plus SOC for treating mNSCLC was evaluated from the perspective of the Chinese healthcare system. Methods: A Markov model with a 15-year time horizon was established and used to comparedeveloped to enable the simulation of treatment-associated costs and patient outcomes when comparing TTFields plus SOC to SOC alone. Primary outcomes for these analyses included total costs, life-years (LYs), quality-adjusted LYs (QALYs), and incremental cost-effectiveness ratio (ICER) values. The impact of paramere uncertainty on model outcomes was evaluated through sensitivity analyses. Additional subgroup and scenario analyses were also performed to extend these results. Results: While TTFields plus SOC exhibited a $74,688 increase in total costs relative to SOC ($96,092 vs. $21,404), it was associated with 0.38 additional QALYs (1.08 vs. 0.82 QALYs) for an ICER of $284,490/QALY. This value exceeded the $35,983/QALY willingness-to-pay (WTP) threshold selected for these analyses by a wide margin. Relative to ICI and DTX treatment, the incremental costs of TTFields plus ICI and TTFields plus DTX were $78,115 and $71,307, respectively, with corresponding gains of 0.42 and 0.13 QALYs, yielding ICERs of $187,434/QALY, and $546,386/QALY. The parameter that most strongly impacted the results of these analyses was the cost of TTFields. Conclusions: The results indicated that given current treatment costs, TTFields plus SOC was insufficiently cost-effective in treating patients with mNSCLC in China, although TTFields plus ICI yields substantial health benefits.